Ayurvedic Management of Subclinical Hypothyroidism - Gautam, Shankar; Padhar, Bharat C; Joshi, Ram Kishor (Journal of Karnali Academy of Health Sciences, 2021)
Subclinical hypothyroidism (SCH), is characterized by normal triiodothyronine (T3), tetraiodothyronine (T4) levels and an abnormal increase of serum thyroid stimulating hormone (TSH). The prevalence of hypothyroidism in the developed world is about 4-5% and that of SCH is about 4- 15% worldwide and it is increasing at an alarming rate. According to Ayurveda, poor function of Jatharagni and Dhatvagni (digestion and metabolism) produces Ama (advance glycation end products (AGEP) and toxic substances). Ama or AGEP interferes with the function of thyroid gland through interaction with thyroid receptors and causes malfunction of thyroid gland. A female patient of 30 years age, having complaints of weight gain, excessive appetite, fatigue, dry skin, irregular oligomenorrhea, and constipation along with 21.25 μIU/ml TSH; diagnosed as case of SCH and treated with Trikatu Powder. The contents of Trikatu Powder like; dry ginger, long pepper, and black pepper have shown their beneficial effect on the thyroid gland, and thus are intended to improve thyroid gland function by preventing the development of AGEP and assisting with digestion and metabolism correction. In the present case study, serum TSH level had been reduced to 4.88 μIU/ml, and decreased weight by 8.5 kgs with improvement in all associated symptoms like excessive appetite, hair fall, constipation, dry skin, oligomenorrhea and fatigue with treatment of Trikatu Powder for 4 months. The outcomes suggest that Trikatu powder may be beneficial to reduce serum TSH level, weight and mitigate associated symptoms in patients of SCH.